(untitled) (American Journal of Islam and Society, 2014)
Sa’diyya Shaikh’s groundbreaking Sufi Narratives of Intimacy: Ibn Arabi, Gender, and Sexuality not only makes a significant contribution to the growing body of scholarship on issues of gender and Islam, but also serves as an eloquent and accessible introduction to the life and work of Muhyi al-Din ibn Arabi, unquestionably one of the most important voices in the Islamic tradition. Moreover, it is a rigorous piece of academic scholarship rooted in a thorough knowledge of Islam’s primary sources and a sophisticated understanding of contemporary methodology, both in the academic study of religion and women and gender studies. At the same time, it adds significantly to normative discussions within Islam – the crucial debates about gender and sexuality, the ongoing arguments on the nature of authority in Islam, and the role of fiqh, kalām, and Sufism within the Muslim tradition. It succeeds brilliantly as a scholarly examination of Ibn Arabi’s work and as an example of feminist scholarship at its very best. For me, the most important aspect is how the book functions as an introduction to the thought of Ibn Arabi, a notoriously demanding thinker whose work can sometimes appear impenetrable. As a result, much of the previous scholarship on him, including the essential and pioneering work of William ...